Spinal manipulation effect on pain and cardiac autonomic modulation in patients with rotator cuff tendinopathy: a pilot study - Silva, Alyssa Conte; Padilha, Juliana Falcão; Marques, Jefferson Luiz Brum; Marques, Cláudia Mirian de Godoy (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: there are few studies that propose to identify the relationship of Vertebral Manipulation (VM) on pain and cardiac autonomic modulation, especially in subjects with rotator cuff injury. Objective: To analyze the effect of chest VM on the pain and cardiac autonomic modulation in patients with rotator cuff (RC). Method: quasi-experimental study with a quantitative approach. Sample of 6 subjects divided into two groups: Asymptomatic Group (AG, n = 3) not presenting shoulder injury and pain complaints and Symptomatic Group (SG, n = 3), with rotator cuff injury. Pain assessment was performed by Visual Analog Scale (VAS) before and after handling, as well as the assessment of Heart Rate Variability (HRV) using an electrocardiogram (ECG) with 8 minutes of duration. Chest VM was held on 4th and 5th thoracic vertebra. The analysis of HRV was performed in the Frequency Domain (VLF-very low frequency, LF-low frequency, HF-high frequency, LF/HF-ratio between low and high frequency). The statistical analysis used the Wilcoxon test for comparison in the same group and the Mann Whitney test for comparison between groups, adopting a 5% significance (p <0.05). Results: There was a reduction of post handling pain, but no statistically significant difference in SG (p=0.317). In HRV the AG showed a decrease VLF (p=0.83) and increased LF (p=0.51), HF (p=0.83) and LF/HF (p=0.51) variables. In the SG, there was an increase in VLF (p=0.83), LF (p=0.83), HF (p=0.51) variables and a decrease in LF/HF (p=0.51) variable. Conclusion: The upper thoracic VM had no effect on the pain and cardiac autonomic modulation in patients with rotator cuff (RC).